Diverse plant promoting bacterial species differentially improve tomato plant fitness under water stress - Zampieri, Elisa; Franchi, Elisabetta; Giovannini, Luca; Brescia, Francesca; Sillo, Fabiano; Fusini, Danilo; Pietrini, Ilaria; Centritto, Mauro; Balestrini, Raffaella (Frontiers in Plant Science, 2023)
Food crops are increasingly susceptible to the challenging impacts of climate change, encompassing both abiotic and biotic stresses, that cause yield losses. Root-associated microorganisms, including plant growth-promoting bacteria (PGPB), can improve plant growth as well as plant tolerance to environmental stresses. The aims of this work were to characterize bacteria isolated from soil and roots of tomato plants grown in open field from a biochemical and molecular perspective, evaluate their PGP potential on tomato plants under controlled conditions, and assess their effects under stress conditions, specifically water deficit. The isolated strains were classified by 16S gene sequencing and exhibited typical features of PGPB, such as the release of siderophores, the production of proteases, and phosphorous solubilization. Inoculating tomato plants with eleven selected strains led to the identification of potentially interesting strains that increased shoot height and dry weight. Three strains were then selected for the experiment under water deficit in controlled conditions. The tomato plants were monitored from biometric and physiological point of view, and the effect of inoculation at molecular level was verified with a targeted RT-qPCR based approach on genes that play a role under water deficit condition. Gene expression analysis revealed a different regulation of genes involved in pathways related to abscisic acid, osmoprotectant compounds and heat shock proteins, depending on the treatments. Furthermore, results showed significant changes in biometric parameters of tomato plants due to the bacterial inoculation, which hold promise for future field applications of these bacterial strains.